Investigation of the Impact of Ddos Attack on Network Efficiency of the University Of Zakho - Sulaiman, Sulaiman M.; Askar, Shavan K. (Science Journal of University of Zakho, 2015)
In this paper an investigation was conducted to have an insight into the impact of the DDoS attack on the network efficiency of the University of Zakho, in particular, after deploying a fiber infrastructure and a datacenter with services such as web server, email server, and ftp server. Tests were conducted on one of the most popular DDoS attacks, that is, the flooding attack that has many types based on the start-of-the-art research in this field. For the evaluation purpose, two Internet services were chosen which are namely; file transfer service and E-learning video service. OPNET was used as a simulation tool to simulate Zakho University network and to conduct attacks because of its high reliability and reputation in this field. Results showed that DDoS attack has a big adverse impact on the legitimate users’ accessibility for both services. Where the file traffic download reduced from 6000 Bytes/s in the case of no attack into only 500 Bytes/s in the case of attack which makes an approximate of 92% loss in the network traffic. In addition, video throughput is reduced from 180KB/s in the case of no attack into less than 20KB/s in the case of attack which makes around 89% loss that is considered a huge degradation in the network performance.
Keywords: Campus Network; DDoS Attack; OPNET